Dynamics of clinical, functional, and immune parameters in patients with myocardial infarction and early fluvastatin administration - V. V. Belov; S. Yu. Bezdol’nova; I. I. Dolgushin (Кардиоваскулярная терапия и профилактика, 2011)
Aim. To assess the interrelations in the dynamics of immune, clinical, and functional parameters among patients with myocardial infarction (MI) and early fluvastatin administration. Material and methods. The study included 129 men, aged from 42 to 67 years (mean age 57 years): 99 MI patients and 30 healthy controls. In all participants, clinical, biochemical, functional, and immune parameters were assessed, with comparisons between healthy individuals vs. MI patients, as well as between MI patients taking fluvastatin (80 mg/d) vs. MI patients not receiving this medication. Results. In men with MI, chronic systemic inflammation was manifested in elevated levels of C-reactive protein, interleukin (IL) 1β, IL8, tumor necrosis factor α, immunoglobulin A and G, and complement components, as well as in decreased levels of IL1 receptor antagonist, CD 3, CD 4, CD 16, and CD 4/CD 8, compared to healthy controls. Early fluvastatin administration (first post-MI hours) was associated with reduced severity of immune disturbances and systemic inflammation. Conclusion. In MI patients, early fluvastatin administration is associated with a significant reduction in systolic and diastolic blood pressure levels, compared to controls, as well as with a substantial increase in exercise capacity at 2 months.